Annexin A2 complexes with S100 proteins: structure, function and pharmacological manipulation - Liu, Yidong (Br J Pharmacol, 2015)
Annexin A2 (AnxA2) was originally identified as a substrate of the pp60v-src oncoprotein in transformed chicken embryonic fibroblasts. It is an abundant protein that associates with biological membranes as well as the actin cytoskeleton, and has been implicated in intracellular vesicle fusion, the organization of membrane domains, lipid rafts and membrane-cytoskeleton contacts. In addition to an intracellular role, AnxA2 has been reported to participate in processes localized to the cell surface including extracellular protease regulation and cell-cell interactions. There are many reports showing that AnxA2 is differentially expressed between normal and malignant tissue and potentially involved in tumour progression. An important aspect of AnxA2 function relates to its interaction with small Ca(2+)-dependent adaptor proteins called S100 proteins, which is the topic of this review. The interaction between AnxA2 and S100A10 has been very well characterized historically; more recently, other S100 proteins have been shown to interact with AnxA2 as well. The biochemical evidence for the occurrence of these protein interactions will be discussed, as well as their function. Recent studies aiming to generate inhibitors of S100 protein interactions will be described and the potential of these inhibitors to further our understanding of AnxA2 S100 protein interactions will be discussed.